The Development of Teaching Material on Integers with Problem-Based Learning Model - Saputro, Bagus Ardi; Fadlilah, Siti Nur; Azizah, Mira (Universitas Pendidikan Indonesia, 2024)
A variety of observations and findings revealed that the current teaching materials for mathematics learning, particularly in the area of integer operations at the elementary school level, are inadequate to meet the learning needs of students. To address this issue, this study was conducted with the goal of developing effective and engaging learning materials for integer operations designed around a Problem-Based Learning (PBL) model. The research involved 17 students and 2 teachers from the 6th grade at SDN 2 Ringin. Data collection was carried out through a combination of observation, interviews, and questionnaires, ensuring a thorough understanding of the teaching and learning environment. The PBL approach was integrated into classroom activities, while the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) guided the systematic development of the materials. Results showed that both students and teachers responded favorably, with experts evaluating the materials as practical and valid. These materials offer a promising alternative for improving mathematics learning in elementary schools.